Several theorems on λ–summable series - Meronen, Olga; Tammeraid, Ivar (Mathematical Modelling and Analysis, 2010)
We prove several propositions on λ‐summable series by Cesàro method (C, 1) or by weighted mean methods N, which are also often called Riesz methods P = (R, pn ). First published online: 09 Jun 2011